2004
DOI: 10.1016/j.febslet.2004.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin suppresses the expression of VEGF, an important factor for angiogenesis, in endothelial cells via degradation of HIF‐1α protein

Abstract: Apigenin, a plant-derived flavone, is a potent inhibitor of cell proliferation and angiogenesis, but the mechanisms leading to the pathological anti-angiogenic effects of apigenin are still unclear. In this study, we found that apigenin inhibited the hypoxia-induced expression of vascular endothelial growth factor (VEGF) mRNA in human umbilical artery endothelial cells. Apigenin also suppressed the expression of erythropoietin mRNA, which is a typical hypoxia-inducible gene, via the degradation of hypoxia-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(67 citation statements)
references
References 30 publications
3
63
0
1
Order By: Relevance
“…A recently published study indeed showed that a much higher concentration of apigenin inhibited HIF-1 activity through inhibition of HIF-1a stabilization. 57 However, as we worked with lower concentrations of apigenin, the results described here are probably more physiologic.…”
Section: Discussionmentioning
confidence: 81%
“…A recently published study indeed showed that a much higher concentration of apigenin inhibited HIF-1 activity through inhibition of HIF-1a stabilization. 57 However, as we worked with lower concentrations of apigenin, the results described here are probably more physiologic.…”
Section: Discussionmentioning
confidence: 81%
“…To investigate the lower limit of oxygen concentrations where C. glutamicum can grow, we used simple anaerobic and microaerobic culture systems, Anaero Pack, as has often been reported (Yano et al 2002;Osada et al 2004;Hagiwara et al 2006). By applying the systems, four representative wild-type strains of C. glutamicum, ATCC 13032, ATCC 14067, ATCC 13869, and ATCC 13870, were examined for their colony-forming abilities on BY agar plates under several oxygen concentrations (0%, 0.5%, 3%, 6%, and atmospheric conditions 21%) in a sealed 2.5-liter box.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is conceivable that chrysin may also inhibit HIF-1a via AKT signaling. It was reported that flavonoids or related compounds, such as apigenin (28,46), resveratrol (47), and (À)-epigallocatechin-3-gallate (48), inhibited expression of HIF-1a through multiple pathways, including protein synthesis and protein degradation. Consistent with previous reports, we show here that chrysin is also multifunctioning in HIF-1a pathway.…”
Section: Discussionmentioning
confidence: 99%